ANALISIS PENGELOLAAN LIMBAH MEDIS PADAT INFEKSIUS DI RUMAH SAKIT X SELAMA MASA PANDEMI COVID-19 TAHUN 2022 - Putri Suryani Rahayu (2022)
During the COVID-19 pandemic, the amount of medical waste generated in Jakarta increased by 30%. Therefore, medical waste management needs to be considered starting from the sorting stage to processing. This study aims to analyze the management of infectious solid medical waste at Hospital X during the COVID-19 pandemic. This research was a qualitative descriptive study with the selection of informants using purposive sampling technique. The results showed that there were two human resources in the management of infectious medical waste at Hospital X, with one person in charge; financing for waste management during the COVID-19 pandemic has also increased; and temporary shelters as well as adequate facilities and infrastructure to manage solid medical waste. The process of managing infectious solid medical waste at Hospital X goes through several stages, such as direct sorting from the source of production, storage in a closed place, transportation in closed vehicles, but still through the general route of patients, and processing using third parties. Effectiveness in the management of infectious solid medical waste in Hospital X is characterized by the absence of accumulation of infectious solid medical waste. Provision of a special line for waste transportation which is separated from the patient route is recommended.